2013
DOI: 10.1186/1476-069x-12-71
|View full text |Cite
|
Sign up to set email alerts
|

Rapid warming in Tibet, China: public perception, response and coping resources in urban Lhasa

Abstract: BackgroundTibet, average altitude more than 4,000 meters, is warming faster than anywhere else in China. The increase in temperatures may aggravate existing health problems and lead to the emergence of new risks. However, there are no actions being taken at present to protect population health due to limited understanding about the range and magnitude of health effects of climate change.MethodsThe study was a cross-sectional survey of 619 respondents from urban Lhasa, Tibet in August 2012 with the aim to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Similar with previous research on risk perceptions of climate change [25,33,34], we found that awareness of the multiple benefits of GHG emission controls on climate and public health was very high (91.9%) in the three cities of this study, likely due to the extensive media coverage, internet penetration and government advocacy on this topic in China. In recent years, awareness raising of low carbon development and green growth has been carried out continuously across the whole country, and it seems that the idea of low carbon transition has been absorbed by the general public [26].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar with previous research on risk perceptions of climate change [25,33,34], we found that awareness of the multiple benefits of GHG emission controls on climate and public health was very high (91.9%) in the three cities of this study, likely due to the extensive media coverage, internet penetration and government advocacy on this topic in China. In recent years, awareness raising of low carbon development and green growth has been carried out continuously across the whole country, and it seems that the idea of low carbon transition has been absorbed by the general public [26].…”
Section: Discussionsupporting
confidence: 89%
“…It should be noted that negative emotions such as fear, guilt and pessimism, are likely to produce passive and defensive responses, and hardly do much to encourage people to change their behaviors or to press for wider social action [8]. Several studies have focused on risk perceptions of climate change, but less attention has been paid to the awareness of the health benefits associated with mitigation actions [33,34]. In addition to providing engaging messages about how to address the problem, ancillary health gains of GHG reductions may also represent climate change mitigation in ways that connect with people’s core ideologies and identities and then anchor it in positive emotions, which is one of the crucial determinants of behavior and behavioral change [8,35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, cooling devices are seldom used in Tibet because heat is not seen to be a serious problem. A survey of 619 respondents that we conducted in Chengguan in 2012 found only 8.7% of participants had air-conditioning at home (Bai et al, 2013). On the basis of the present study, and projections for future climate change in Tibet, we recommend an officially sanctioned and comprehensive temperature adaption plan.…”
Section: Lagmentioning
confidence: 91%
“…The Qinghai-Tibetan Plateau (QTP) is one of the most sensitive and vulnerable areas suffering intense climate change impacts. Average temperatures in the QTP kept rising since the 1960s (Bai et al, 2013). And worse, the warming has accelerated during recent decades, especially in the last 20 years (Wei and Fang, 2013).…”
Section: Introductionmentioning
confidence: 99%